Root-knot nematodes on tannia (Xanthosoma sagittifolium) - Caveness, F.E.; Wilson, J.E.; Terry, E. (1981)
Root-knot nematodes (Meloidogyne spp.) are common pests in tropical soils and cause yield reduction in many major food crops. Steiner (1931) was the first to observe root-knot nematode parasitizing Xanthosoma sp. and later Brathwaite (1972) and Naylor (1974) reported root-knot nematode attacking tannia. Acosta (1979) reported high populations of M. incognita juveniles in the cortex tissue of Xanthosoma sp. in Puerto Rico. However, yield reductions were not referred to in any of these reports. Therefore, a trial was initiated to determine the effects of parasitism by the root-knot nematode, M. incognita, race 2 (Sasser and Triantaphyllou, 1977) on the growth of tannia.